Nebulized Magnesium Sulphate Versus Saline as an Adjuvant in Acute Exacerbation of Chronic Obstructive Pulmonary Disease in a Tertiary Centre of Nepal: A Randomized Control Study - Bajracharya, Manjita; Acharya, Ramesh P; Neupane, Ram P; Sthapit, Rekha; Tamrakar, Apurva R (Journal of Institute of Medicine Nepal, 2021)
Introduction Magnesium has been shown to have bronchodilator properties in asthma and chronic obstructive pulmonary disease (COPD). Therapeutic benefits of nebulized magnesium in asthma has been seen. The purpose of this study was to compare therapeutic benefits of nebulised magnesium sulphate as an adjuvant with normal saline in patients with COPD exacerbation.MethodsIt was a randomized single blind interventional study of 172 cases of acute exacerbation of COPD presenting (AECOPD) with a peak expiratory flow rate (PEFR)